Usage Of ‘ICT’ in English Language Teaching - Jumayeva Nilufar Xudoyor qizi (Zeta Repository, 2023)
Today, science and ICT (information and communication technology) affect all facets of human life. Science and technology have significantly impacted the majority of developments observed in the modern era. Even in the education sector, technological progress and innovations have had a noticeable impact and altered the landscape. Traditional approaches to higher education delivery have become less engaging. Here, technology plays a crucial role in fostering student innovation and motivation (Stockwell, 2016). The term "ICT" encompasses all forms of communication technology, including computers, mobile phones, radio, television, and satellite systems. It relates to the Internet infrastructure. As educators become more aware of technology’s capacity to facilitate independent and collaborative learning environments in which students can acquire English with relative ease, its role and application as a teaching tool for the English language are expanding. The use of ICT in the teaching and learning process is imperative, and teachers are expected to be innovative and enthusiastic when integrating ICT into their teaching and learning processes. A teacher must consider the use of technology in the classroom